2007
DOI: 10.1080/02688690701364781
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of microtubule associated protein-2 degradation after mild head injury by mexiletine and calpain-2 inhibitor

Abstract: The objective of the study was to address the early effects of mild, closed, head injuries on neuronal stability and the prevention of microtubule-associated protein-2 (MAP-2) degradation by mexiletine and calpain-2 inhibitor. Twenty-four rats were divided into four groups: control group (1); trauma group without treatment (2); mexiletine-pretreated and subjected to trauma group (3); trauma subjected and then calpain-2 inhibitor received group (4). All animals were subjected to mild, closed, head trauma. Front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(42 reference statements)
0
11
0
1
Order By: Relevance
“…To identify functionally relevant downstream molecular targets of calpain activation during AAD, we evaluated the expression levels of different proteins that had previously been reported to be cleaved by calpain in other model systems232425262728. Based on previous studies of our group and others110, we focused on proteins that are involved in autophagy, cytoskeleton integrity and axonal transport as these processes are pivotal for axonal degeneration.…”
Section: Resultsmentioning
confidence: 99%
“…To identify functionally relevant downstream molecular targets of calpain activation during AAD, we evaluated the expression levels of different proteins that had previously been reported to be cleaved by calpain in other model systems232425262728. Based on previous studies of our group and others110, we focused on proteins that are involved in autophagy, cytoskeleton integrity and axonal transport as these processes are pivotal for axonal degeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, MAP-2 immunostaining has been widely applied to label the dendritic meshwork and to estimate the dynamic changes in dendritic architecture. Previous studies have shown that MAP-2 degeneration is related to lipid peroxidation and calcium-related calpain activation (Ercan et al, 2001; Atalay et al, 2007). PROG is protective against excitotoxicity by reducing N-methyl-D-aspartate (NMDA), glutamate and excitatory cholinergic signaling, and by balancing Ca 2+ mobilization (Cai et al, 2008; Hu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The most well-studied nonproprietary potential biomarkers for TBI and stroke include S-100b [55][56][57][58][59][60][61] neuron-specific enolase (NSE) [62][63][64][65], glial fibrillary acidic protein (GFAP) [66][67][68], and SBDPs [69][70][71][72][73]. More recent studies in TBI biomarkers include, UCH-L1, MAP-2, and TAU proteins [47,74,75]. Below is the description of the major identified putative biomarkers in the area of TBI.…”
Section: Current Status Of Brain Injury Biomarker Researchmentioning
confidence: 99%